2016
DOI: 10.1007/978-3-319-31733-5_18
|View full text |Cite
|
Sign up to set email alerts
|

Geologic, Hydrothermal, and Geochemical Relationships Between Bimodal Magmatism and Massive Sulphide Mineralization in the Central Jebilet-Guemassa Province (Western Moroccan Hercynides)

Abstract: The Jebilet-Guemassa volcanic-hosted massive sulphide (VHMS) province comprises four sheet-like, polymetallic deposits. These are referred to as Kettara (>20 Mt at 0.6 % Cu with traces of Pb and Zn), Hajar (*20 Mt at 10.5 % Zn, 3.2 % Pb, 0.6 % Cu, and 60 g/t Ag), Draa Sfar (*11 Mt at 5.9 % Zn, 2.2 % Pb, and 0.3 % Cu), and Koudiat Aicha (3-5 Mt at 3 % Zn, 1 % Pb, and 0.6 % Cu), which collectively total >80 Mt of Pb-Zn-Cu ore. Host rocks consist predominantly of variably altered, mafic to felsic, submarine volca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…While most of the values could be compatible with the leached H 2 S derived from magmatic sulfides, the outliers could be explained by H 2 S being supplied and derived from the leaching of sulfides of biogenic origin, i.e. a source of sulfur prevailing in the organic-rich shales recommended as metallic sources (Bouabdellah et al, 2016). massive sulfide deposits in central Jebilet (North of Marrakech, Morocco).…”
Section: Section 1: Minerals and Mineralizationmentioning
confidence: 81%
See 2 more Smart Citations
“…While most of the values could be compatible with the leached H 2 S derived from magmatic sulfides, the outliers could be explained by H 2 S being supplied and derived from the leaching of sulfides of biogenic origin, i.e. a source of sulfur prevailing in the organic-rich shales recommended as metallic sources (Bouabdellah et al, 2016). massive sulfide deposits in central Jebilet (North of Marrakech, Morocco).…”
Section: Section 1: Minerals and Mineralizationmentioning
confidence: 81%
“…The mixing of such a fluid with a serpentinite-derived fluid may have led to As and S (Maacha, 1994 ;Maacha et al, 1998 ;Maacha, 2013). It is also suggested that black shale of the Imiter Group could be the source of all metals and As (Bouabdellah et al, 2016). ( 7) The sequence of mineral precipitation with decreasing temperatures and salinities within the advancing paragenetic sequence could also have been driven by the redox-dependent solubility of Co and Ni (Scholten et al, 2018).…”
Section: Section 1: Minerals and Mineralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize, the past production and total resources of the massive sulphide deposits of the Moroccan Meseta are estimated to be more than 80 Mt [64], with some deposits reaching a depth of 1500 m. Most of these deposits have been classified as VMS deposits [18][19][20][21][22][23]. The dominance of pelitic rocks in the wall rock and the presence of felsic volcanic rocks in the Tazakourt orebody led Marcoux et al [18] to classify the Draa Sfar deposit within the pelitic subgroup of the siliciclastic-felsic type of Franklin et al [3].…”
Section: Size and Tonnagementioning
confidence: 99%
“…Nevertheless, Marcoux et al [18] and Bouabdellah et al [64] consider that the least radiogenic signatures are similar to those of the Visean igneous rocks of the Iberian Pyrite Belt and the eastern Meseta, and they suggest a major contribution of volcanic rocks as a source of metals. The lead isotope signature of the Cu-rich lens at Draa Sfar plots close to the Zartman and Doe [138] upper crust evolutionary curve, and it suggests that most of the lead is inherited from the hosting Sarhlef Schists [18,64]. A magmatic source of metals is strengthened by the fact that the less radiogenic signatures are recorded in Draa Sfar South and Hajjar deposits, which are associated with volcanic rocks.…”
Section: The Origin Of Metalsmentioning
confidence: 99%